Optical properties of lithium borate glass (Li2O)x (B2O3)1-x - Mohamed Kamari, Halimah; Chiew, W. H.; Abd. Aziz, Sidek; Wan Yusoff, Wan Mohamad Daud; Abd. Wahab, Zaidan; Matori, Khamirul Amin; Mustafa, Iskandar Shahrim (Universiti Kebangsaan Malaysia, 2014)
A series of (Li2O)x(B2O3)1-x has been synthesized with mole fraction x=0.10, 0.15,0.20,0.25 and 0.30 mol% using melt quenching method. The structure of the glass system was determined by FTIR and X-ray diffraction. The density and molar volume were determined and the density increases with Li2O content whereas molar volume decreases with Li2O. Refractive index of glass samples were measured by ellipsometer. Refractive index increases with increase of Li2O. The absorption spectra of the studied glass showed that position of fundamental absorption edge shifts to longer wavelength with Li2O. Optical band gap varies from 0.10 to 2.22 eV and Urbach energy varies from 2.91 to 1.55 eV. The variation in optical band gap and Urbach energy were due to the variation in the glass structure.